Prevalence of nodal metastases in lymph node stations 8 & 9 in a large UK lung cancer surgical centre without routine pre-operative EUS nodal staging. (January 2018) - Evison, Matthew; Edwards, Tim; Balata, Haval; Tempowski, Alex; Teng, Benjamin; Bishop, Paul; Fontaine, Eustace; Krysiak, Piotr; Rammohan, Kandadai; Shah, Rajesh; Crosbie, Philip; Booton, Richard
Highlights: The prevalence of station 8/9 nodal metastases is low (approximately 5%). This is despite a lack of routine pre-operative EUS. 65% of station 8/9 metastases are part of multi-station N2 disease. 2% of patients have N2 disease only accessible endoscopically with EUS. Abstract: Introduction: Endoscopic ultrasound (EUS) allows access to the inferior mediastinal lymph node stations (8 and 9) which are beyond the reach of endobronchial ultrasound (EBUS). The addition of EUS to EBUS procedures requires cost and resource investment. This study sought to describe the prevalence of station 8/9 nodal metastases from intra-operative lymph node sampling in a UK region where routine pre-operative EUS is not available. Methods: A retrospective review of all lung cancer resections at the University Hospital South Manchester from 2011 to 2014. Surgical variables, pre-operative PET variables and survival outcomes were collected and analysed. Results: 1421 surgical resections were performed in the study period. Lymph node stations 8 and/or 9 were sampled in 52% (736/1421) of patients. Overall, there were 34 patients with lymph node metastases at station 8/9. This represents 2.4% of the study populations and 4.6% of patients in whom stations 8/9 were sampled intra-operatively. Of those patients with station 8/9 metastases, 65% (22/34) had multi-station N2 disease and the majority of the additional N2 disease was present in EBUS-accessible areas (lymph node stations 2, 4 and 7). Two percent (16/736) of patients in whom station 8/9 lymph nodes were sampled intra-operatively had N2 disease that was only accessible endoscopically with EUS. There was no significant difference in overall survival in patients with pathological N2 disease stratified according to whether stations 8/9 were involved or not. Conclusions: The prevalence of lymph node metastases in stations 8/9 in this UK surgical centre where routine pre-operative EUS is not performed is low at approximately 5%. Given the identification of N2 disease in two-thirds of these patients can potentially be achieved through EBUS alone, this questions whether the resource implications of EUS are justified by the impact on patient management.